Biodegradable material as well as preparation method and application thereof

By optimizing the formulation and process, the poor compatibility and dispersion in the modification of polyglycolic acid-based materials were solved, and high-strength degradable films were prepared, which solved the problem of insufficient mechanical properties of the films in the prior art, and achieved high Filling function and low cost production.

CN119144125APending Publication Date: 2024-12-17CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310710900.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing polyglycolic acid-based materials have problems of poor compatibility and dispersion during the modification process, which leads to a significant reduction in mechanical strength and makes it difficult to prepare high-strength degradable films.

Method used

By optimizing the formulation system and process, adding a specific amount of coupling agent to improve the interaction between inorganic fillers and resins, and through a two-step processing process, the inorganic fillers are better dispersed, and the introduction of compatible agents improves polyglycolic acid and biological Compatibility between degradable ester polymers, a high-fill function masterbatch was prepared and melt-extruded to obtain a high-strength blown film modified material.

Benefits of technology

The dispersion of inorganic fillers and the mechanical properties of the film are significantly improved, and film materials with better comprehensive mechanical properties are obtained, taking into account the good film mechanical strength and toughness, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004287616850000091
    Figure BDA0004287616850000091
  • Figure BDA0004287616850000101
    Figure BDA0004287616850000101
Patent Text Reader

Abstract

The invention discloses a biodegradable material as well as a preparation method and application thereof. The method for preparing the biodegradable material comprises the following steps: (1) melting and blending 30-70 parts by weight of biodegradable ester polymer, 30-70 parts by weight of inorganic filler and 1-5 parts by weight of coupling agent to obtain a master batch; and (2) carrying out melt blending on 10-50 parts by weight of polyglycolic acid, 10-80 parts by weight of a biodegradable ester polymer, 30-60 parts by weight of the master batch and 0.5-10 parts by weight of a compatilizer to obtain the biodegradable material. According to the invention, the dispersibility of the inorganic filler and the matrix is obviously improved, and the prepared film has good mechanical properties and can be used in the fields of biodegradable packaging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biodegradable materials and relates to a biodegradable material and a preparation method and application thereof. Background Art

[0002] Polyglycolic acid (PGA for short) is an aliphatic polyester polymer material with the least carbon unit number, a completely decomposable ester structure, and the fastest degradation rate. Polyglycolic acid has excellent gas barrier properties, excellent mechanical strength and outstanding degradability, and can be used in fields such as degradable packaging to solve the problem of white pollution. However, due to the disadvantages of PGA such as high brittleness and low melt strength, its processing and application in many fields (such as films, etc.) are seriously restricted. In addition, the high cost of biodegradable materials limits its promotion and application. Therefore, it is necessary to modify PGA to obtain a degradable film with good processability, excellent mechanical properties and low cost. However, during the modification process, poor compatibility and poor dispersibility between components will lead to insufficient mechanical properties of the film.

[0003] CN109575536A discloses a modified polyglycolic acid biodegradable mulch film, which is made of the following raw materials in parts by mass: 15-45 parts of polyglycolic acid, 40-80 parts of polybutylene succinate-co-butylene terephthalate (PBST), 5-15 parts of compatibilizer, 0.5-1.5 parts of lubricant, 0.5-1 parts of anti-hydrolysis agent, 0.1-0.5 parts of antioxidant, 0.1-0.5 parts of anti-photoaging agent, 0.5-1 parts of antibacterial agent, 5-20 parts of lightweight modified composite material; wherein the lightweight modified composite material is made of 0.1-0.5 parts of epichlorohydrin, 1-2 parts of β-cyclodextrin, 1-2 parts of potassium aluminum silicate, and 5-10 parts of mesoporous silica. The purpose of the invention is to provide a modified polyglycolic acid biodegradable mulch film with low density, excellent heat preservation and moisture retention performance, in which a variety of additives are added, and the mechanical properties of the mulch film are not paid attention to.

[0004] CN110016216A discloses a fully degradable polyglycolic acid composite packaging material, which is made of the following weight parts: polyglycolic acid 80-100, polycaprolactone 45-60, poly(L-lactide-ε-caprolactone) 2-5, pentaerythritol diphosphite 0.03-0.2, opening agent 0.2-1, slip agent 0.05-2, toughening agent 1-7, water blocking agent 0.5-11, chitosan 2-6, starch 15-35 and reinforcing fiber 1-5. The elongation at break of the material disclosed in the invention is low, and the highest is only 105%.

[0005] CN113088055A discloses a high-performance polyglycolic acid-based composite material and a preparation method thereof, wherein the preparation comprises the following process: preparing the following components by weight: 50-95 parts of polyglycolic acid, 5-50 parts of tough degradable polyester, 0.5-30 parts of functional filler, 0.01-10 parts of compatibilizer, 0-3 parts of antioxidant, 0-1 parts of lubricant, and 0-1 parts of chain extender;

[0006] Preparation by method 1: firstly, the biodegradable polyester A and the compatibilizer are mixed according to the weight ratio, and melt-blended to obtain a blended masterbatch; then, the polyglycolic acid, the blended masterbatch, the functional filler, the antioxidant, the lubricant and the chain extender are pre-mixed and melt-blended through a twin-screw extruder to obtain a polyglycolic acid-based composite material;

[0007] Or, prepare by method 2:

[0008] The polyglycolic acid, the degradable polyester A, the functional filler, the compatibilizer, the antioxidant, the lubricant and the chain extender are uniformly mixed in proportion by weight to obtain a premix, and then the premix is ​​melt-blended to obtain a polyglycolic acid-based composite material;

[0009] The degradable polyester A is at least one of polylactic acid, adipic acid / butylene terephthalate copolymer, polycaprolactone, polybutylene succinate, polyhydroxyalkanoate, polybutylene succinate / adipate copolymer, and carbon dioxide-based copolymer. The invention significantly improves the interfacial interaction between the polyglycolic acid matrix and the degradable polyester B by adding a compatibilizer, and further significantly improves the toughening effect of the degradable polyester B by cooperating with a specific blending process; in addition, by adding functional fillers, an in-situ reaction occurs between the polyglycolic acid matrix, promoting dispersion, and improving the crystallization effect and heat resistance. However, the elongation at break of the polyglycolic acid-based composite material disclosed in the invention is low, with a maximum of only 86%.

[0010] Existing polyglycolic acid-based materials generally have problems with poor system compatibility and dispersibility after adding various modifiers, resulting in a significant decrease in mechanical strength. Summary of the invention

[0011] In view of the problem of poor dispersibility of modifiers in the modification of polyglycolic acid-based materials in the prior art, the present invention improves the dispersibility of inorganic fillers by optimizing the formulation system and process, and the prepared material has good film blowing performance and can obtain a film with better comprehensive mechanical properties.

[0012] To achieve the purpose, the present invention provides the following technical solutions:

[0013] One aspect of the present invention provides a method for preparing a biodegradable material, comprising the following steps:

[0014] (1) melt-blending 30-70 parts by weight of a biodegradable ester polymer, 30-70 parts by weight of an inorganic filler, and 1-5 parts by weight of a coupling agent to obtain a masterbatch;

[0015] (2) melt-blending 10-50 parts by weight of polyglycolic acid, 10-80 parts by weight of a biodegradable ester polymer, 30-60 parts by weight of the masterbatch and 0.5-10 parts by weight of a compatibilizer to obtain a biodegradable material.

[0016] The present application optimizes the formulation system, adds a specific amount of coupling agent to the formulation system to improve the interaction between the inorganic filler and the resin, and firstly blends the inorganic filler, coupling agent and biodegradable ester polymer according to specific amounts to obtain a highly filled functional masterbatch. Then, polyglycolic acid, biodegradable ester polymer, functional masterbatch and compatibilizer are melt-extruded according to specific amounts to obtain a blown film modified material. The introduction of a compatibilizer into the formulation system is beneficial to improving the compatibility between polyglycolic acid and biodegradable ester polymer. And through a two-step processing technology, in conjunction with the formulation system of the present invention, the inorganic filler can be better dispersed, reducing the loss of mechanical properties of the film, which is beneficial to the preparation of a high-strength film.

[0017] In the present invention, the amount of the biodegradable ester polymer used in preparing the masterbatch in step (1) is 30-70 parts by weight, for example, 30, 40, 50, 60, 70 parts by weight, etc. In step (2), the amount of the biodegradable ester polymer used for blending is 10-80 parts by weight, for example, 10, 20, 30, 40, 50, 60, 70, 80 parts by weight, etc. In the formulation system of the present invention, adding the above-mentioned amount of biodegradable ester polymer in steps (1) and (2) respectively is conducive to taking into account good film mechanical strength and toughness. If too much is added, the film mechanical strength will be insufficient, and too little will lead to insufficient film toughness. In some embodiments, the amount of the biodegradable ester polymer used in step (1) is 30-50 parts by weight, and the amount of the biodegradable ester polymer in step (2) is 50-70 parts by weight.

[0018] In the present invention, the amount of inorganic filler in step (1) is 30-70 parts by weight, for example, 30, 40, 50, 60, 70 parts by weight, etc. In some embodiments, for example, it is 50-70 parts by weight. The above-mentioned amount of inorganic additive is used in combination with other components to prepare biodegradable materials through the method of the present invention. The inorganic filler can be well dispersed, which is not only beneficial to reducing the cost of the film, but also can take into account the better comprehensive mechanical properties of the material. If too much is added, it will affect the mechanical properties of the film, and too little will make it difficult to reduce the production cost.

[0019] In the present invention, the amount of coupling agent in step (1) is 1-5 parts by weight, for example, 1, 2, 3, 4, 5 parts by weight, etc., and in some embodiments, for example, 1-2 parts by weight. The above amount of coupling agent is used in combination with other components to prepare biodegradable materials by the method of the present invention, which can not only improve the interaction between the inorganic filler and the matrix, but also take into account better material properties. If too much is added, it may affect the overall material properties, and too little will be detrimental to the uniform dispersion of the inorganic filler.

[0020] In the present invention, in step (2), the amount of the compatibilizer is 0.5-10 parts by weight, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 parts by weight, etc., and in some embodiments, for example, 1-3 parts by weight. The compatibilizer in the above amount is used in combination with other components to prepare the biodegradable material by the method of the present invention, which is beneficial to enhance the compatibility between PGA and the biodegradable ester polymer. If too much is added, the melt index will be too low and the processability will be poor. If too little is added, the volume-increasing effect will not be achieved.

[0021] In some embodiments, in step (1), the biodegradable ester polymer is 30-50 parts by weight (e.g., 30, 40, 50 parts by weight or a value and range between any two of these values), the inorganic filler is 50-70 parts by weight (e.g., 50, 60, 70 parts by weight or a value and range between any two of these values), and the coupling agent is 1-2 parts by weight (e.g., 1, 2 parts by weight or a value and range between any two of these values);

[0022] In step (2), the polyglycolic acid 20-40 parts by weight (e.g., 20, 30, 40 parts by weight or a value and range between any two of these values), the biodegradable ester polymer 50-70 parts by weight (e.g., 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 parts by weight or a value and range between any two of these values), the masterbatch 4 The invention relates to a polyol having a plurality of weight parts and a plurality of weight parts of a compatibilizer. The polyol has a plurality of weight parts and a plurality of weight parts of a compatibilizer. The polyol has a plurality of weight parts and a plurality of weight parts of a compatibilizer.

[0023] In some preferred embodiments, the polyglycolic acid is a homopolymer with a weight average molecular weight of 50,000-300,000, preferably 130,000; the melt index of the polyglycolic acid at 240°C and 2.16 kg load is 5-36 g / 10 min, preferably 26 g / 10 min; the melting point of the polyglycolic acid is 218-230°C, preferably 220-225°C.

[0024] In some embodiments, the biodegradable ester polymer is selected from one or more of polylactic acid, polybutylene succinate, polycaprolactone, polycarbonate, and polybutylene terephthalate / adipate.

[0025] In some embodiments, the inorganic filler is selected from one or more of talc, silicon dioxide, montmorillonite, clay, calcium carbonate, and microcrystalline cellulose.

[0026] In some embodiments, the coupling agent is selected from one or more of silane coupling agents, phthalates, and maleic anhydride graft copolymers. Preferably, the grafting rate of the maleic anhydride graft copolymer is 0.2-5% by weight, preferably 0.5-1% by weight.

[0027] In some embodiments, the compatibilizer is selected from one or more of epoxy compounds and polyisocyanate compounds.

[0028] Preferably, the epoxy compound is a copolymer containing a glycidyl methacrylate group, more preferably selected from at least one of styrene-acrylonitrile-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer, POE elastomer-glycidyl methacrylate copolymer, and styrene-methacrylate-glycidyl methacrylate copolymer; wherein the content of glycidyl methacrylate is 5-15% by weight, preferably 7-12% by weight.

[0029] Preferably, the polyisocyanate compound is selected from one or more of toluene-2,4-diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, and lysine diisocyanate.

[0030] In some embodiments, in step (1), the melt blending conditions include: a temperature of 180-220° C., preferably 190-210° C.; an extruder speed of 50-150 rpm, preferably 70-120 rpm;

[0031] In step (2), the conditions for melt blending include: temperature of 220-260° C., preferably 220-250° C.; extruder speed of 50-150 rpm, preferably 80-120 rpm.

[0032] Preferably, the method specifically comprises the following steps: drying the raw material before use, firstly blending the biodegradable ester polymer, inorganic filler and coupling agent in step (1) to obtain the masterbatch, and then blending the polyglycolic acid, biodegradable ester polymer, the masterbatch and compatibilizer in step (2) to melt extrude;

[0033] Further preferably, the drying conditions include: drying temperature of 40-80° C.; drying time of 4-10 h.

[0034] The present invention also provides a biodegradable material prepared by the method described above.

[0035] Another aspect of the present invention provides a method for preparing a biodegradable film, comprising the steps of blowing the biodegradable material described above to obtain a biodegradable film;

[0036] Preferably, the film blowing conditions include: a temperature of 180-240° C., preferably 190-220° C.; and a blowing ratio of 1-4, preferably 1.5-3.

[0037] The present invention also provides a biodegradable film prepared by the method described above.

[0038] In another aspect, the present invention also provides the application of the above-mentioned biodegradable material or the above-mentioned biodegradable film in the field of packaging. For example, the biodegradable film can be used in shopping bags, food packaging and other fields involving packaging needs.

[0039] The technical solution provided by the present invention has the following beneficial effects:

[0040] The method of the present invention is used to prepare biodegradable materials and further prepare them into film materials, which can improve the compatibility and dispersibility of the components in the system, especially improve the dispersibility of inorganic fillers, and obtain materials with better film blowing performance and films with higher comprehensive mechanical properties. DETAILED DESCRIPTION

[0041] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0042] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0043] The present invention will be further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0044] Polyglycolic acid (PGA) is a product of Shanghai Pujing Chemical Technology Co., Ltd. It has a weight average molecular weight of 130,000, a melt index of 26 g / 10 min (240°C, 2.16 kg), and a melting point of 220°C. It is a homopolymer of glycolic acid.

[0045] Polybutylene terephthalate-adipate (PBAT), BASF C1200, is a BASF product with a melt index of 2.7-4.9 g / 10 min (190°C, 2.16 kg) and a melting point of 110-120°C.

[0046] The compatibilizer ADR-4468 is a BASF product, which is a styrene-methacrylate-glycidyl methacrylate copolymer, the content of glycidyl methacrylate is 10% by weight, and the molecular weight is 6,800.

[0047] Talc powder is a product of Changzhou Rongao Chemical New Materials Co., Ltd., 2500 mesh.

[0048] The coupling agent GR216 is a product of Dow Chemical, which is a maleic anhydride (MAH) grafted elastomer POE (ethylene and octene copolymer) with a grafted maleic anhydride content of 0.5-1% by weight.

[0049] Silane coupling agent KH550 is a product of Shandong Hengyu New Materials Co., Ltd.

[0050] Extensional rheology test:

[0051] The HAAKE MARS of Thermo Fisher Scientific was used for the tensile rheological test: the tensile rate was fixed at 0.11 / s, and the tensile rheological test was carried out in the range of 210-250℃, from 100s -1 Scan to 0.5s -1 , observe the change of extensional viscosity with time, and record the extensional viscosity at 30s.

[0052] Mechanical strength test:

[0053] According to the GB / T 1040.3-2006 test standard, the samples were cut into corresponding tensile strips, and the film tensile test was carried out on a universal tensile machine with a test speed of 250mm / min to obtain the tensile breaking strength and elongation at break of the film. Five strips were taken in the horizontal and vertical directions, and the average value was calculated.

[0054] Film blowing process:

[0055] The modified material is melted and extruded through an extruder to a film head of a blow molding machine, and is blown upward by the film head to form a film bubble, which is then rolled up to obtain a film.

[0056] In the following examples and comparative examples, PGA, PBAT, compatibilizer ADR-4468, coupling agent and inorganic filler (such as talc and silica) were dried in a vacuum drying oven before use at a drying temperature of 80° C. for 4 h.

[0057] Example 1

[0058] 5 kg PBAT, 5 kg talc and 0.1 kg silane coupling agent KH550 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 190-210° C., and extrusion granulation was performed to obtain a masterbatch.

[0059] 2kg PGA, 5kg PBAT, 6kg masterbatch, and 0.3kg compatibilizer ADR-4468 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed to obtain a modified material, and the modified material was subjected to a tensile rheology test. The results are shown in Table 1.

[0060] The modified material was subjected to a film blowing process at a film blowing temperature of 210°C and a blow-up ratio of 2.0 to obtain a film. The film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0061] Example 2

[0062] 5 kg PBAT, 5 kg talc and 0.1 kg coupling agent GR216 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 190-210° C., and extrusion granulation was performed to obtain a masterbatch.

[0063] 2kg PGA, 5kg PBAT, 6kg masterbatch, and 0.3kg compatibilizer ADR-4468 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed to obtain a modified material, and the modified material was subjected to a tensile rheology test. The results are shown in Table 1.

[0064] The modified material was subjected to a film blowing process at a film blowing temperature of 210°C and a blow-up ratio of 2.0 to obtain a film. The film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0065] Example 3

[0066] 5 kg PBAT, 5 kg silica and 0.2 kg coupling agent GR216 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 190-210° C., and extrusion granulation was performed to obtain a masterbatch.

[0067] 2kg PGA, 5kg PBAT, 6kg masterbatch, and 0.3kg compatibilizer ADR-4468 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed to obtain a modified material, and the modified material was subjected to a tensile rheology test. The results are shown in Table 1.

[0068] The modified material was subjected to a film blowing process at a film blowing temperature of 210°C and a blow-up ratio of 2.0 to obtain a film. The film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0069] Example 4

[0070] 3kg PBAT, 7kg talc and 0.2kg coupling agent GR216 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 190-210°C, and extrusion granulation was performed to obtain a masterbatch.

[0071] 2kg PGA, 6.7kg PBAT, 4.3kg masterbatch, and 0.3kg compatibilizer ADR-4468 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed to obtain a modified material, and the modified material was subjected to a tensile rheology test. The results are shown in Table 1.

[0072] The modified material was subjected to a film blowing process at a film blowing temperature of 210°C and a blow-up ratio of 2.0 to obtain a film. The film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0073] Comparative Example 1

[0074] 2kg PGA, 8kg PBAT, 3kg talc and 0.3kg compatibilizer ADR-4468 were stirred and mixed by a high-speed mixer, and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed to obtain a comparative modified material, and the comparative modified material was subjected to a tensile rheological test. The results are shown in Table 1.

[0075] The comparative modified material was subjected to a film blowing process at a film blowing temperature of 210° C. and a blow-up ratio of 2.0 to obtain a comparative film. The comparative film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0076] Comparative Example 2

[0077] 2kg PGA, 8kg PBAT, 3kg talc, 0.06kg silane coupling agent KH550 and 0.3kg compatibilizer ADR-4468 were stirred and mixed by a high-speed mixer, and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed, and a comparative modified material was obtained. The comparative modified material was subjected to a tensile rheological test, and the results are shown in Table 1.

[0078] The comparative modified material was subjected to a film blowing process at a film blowing temperature of 210° C. and a blow-up ratio of 2.0 to obtain a comparative film. The comparative film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0079] Comparative Example 3

[0080] 2kg PGA, 8kg PBAT, 3kg talc, 0.06kg coupling agent GR216 and 0.3kg compatibilizer ADR-4468 were stirred and mixed by a high-speed mixer, and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed, and a comparative modified material was obtained. The comparative modified material was subjected to a tensile rheological test, and the results are shown in Table 1.

[0081] The comparative modified material was subjected to a film blowing process at a film blowing temperature of 210° C. and a blow-up ratio of 2.0 to obtain a comparative film. The comparative film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0082] Comparative Example 4

[0083] 10 kg PBAT and 0.375 kg compatibilizer ADR-4468 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm and the screw extrusion blending temperature was 190-210° C., and extrusion granulation was performed to obtain a comparative masterbatch.

[0084] 2kg PGA, 8kg comparison masterbatch, 3kg talcum powder and 0.06kg coupling agent GR216 were stirred for 3 minutes in a high-speed stirrer and then melt-blended by a twin-screw extruder, wherein the screw speed was 100 rpm, the screw extrusion blending temperature was 220-250°C, extrusion granulation was performed to obtain a comparison modified material, and the comparison modified material was subjected to a tensile rheology test. The results are shown in Table 1.

[0085] The comparative modified material was subjected to a film blowing process at a film blowing temperature of 210° C. and a blow-up ratio of 2.0 to obtain a comparative film. The comparative film was subjected to a mechanical strength test, and the results are shown in Table 1.

[0086] Table 1

[0087]

[0088]

[0089] From the above results, it can be seen that compared with Example 1, Example 1-4 uses the formulation system and process of the present invention, adds a coupling agent, and optimizes the masterbatch preparation method, based on the proportion of inorganic fillers in the formulation system. Compared with Examples 1-4, based on the equivalent proportion of inorganic fillers, although coupling agents are also introduced into the formulation system, Comparative Examples 2-3 are not prepared using the preparation process of the present invention, and the inorganic fillers are not introduced into the preparation procedure in the form of a masterbatch together with the coupling agent. As a result, the obtained modified material cannot take into account the improvement of the tensile viscosity and the comprehensive mechanical properties of the film. Compared with Examples 1-4, although a masterbatch is also prepared in Comparative Example 4, the inorganic fillers and coupling agents are not introduced into the preparation procedure in the form of a masterbatch. As a result, the obtained modified material is significantly inferior to Examples 1-4 of the present invention in terms of tensile viscosity and comprehensive mechanical properties of the film.

[0090] From the above experimental results, it can be seen that compared with comparative examples 1-4, based on the same inorganic filler ratio, adding the inorganic filler and the coupling agent together in the form of a masterbatch into the preparation system helps to improve the dispersion of the inorganic filler, which is beneficial to both improve the tensile viscosity of the modified material and the comprehensive mechanical strength of the film. In examples 1-4, changing the type of inorganic filler and the content of the masterbatch can adjust the tensile viscosity of the modified material and the mechanical strength of the film.

[0091] The present invention has been described with reference to the embodiments and examples. However, the present invention is not limited to the aspects described in the above embodiments and examples, and various modifications may be made. It should be understood that it is possible for those skilled in the art to make various modifications and equivalent substitutions to the present invention without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments described herein. More specifically, the scope of protection of the present invention is defined by the appended claims.

Claims

1. A method for preparing a biodegradable material, characterized in that: The steps include: (1) melt-blending 30-70 parts by weight of a biodegradable ester polymer, 30-70 parts by weight of an inorganic filler, and 1-5 parts by weight of a coupling agent to obtain a masterbatch; (2) melt-blending 10-50 parts by weight of polyglycolic acid, 10-80 parts by weight of a biodegradable ester polymer, 30-60 parts by weight of the masterbatch and 0.5-10 parts by weight of a compatibilizer to obtain a biodegradable material.

2. The method according to claim 1, characterized in that In step (1), the amount of the biodegradable ester polymer is, for example, 30-50 parts by weight, the amount of the inorganic filler is, for example, 50-70 parts by weight, and the amount of the coupling agent is, for example, 1-2 parts by weight; In step (2), the amount of the polyglycolic acid is, for example, 20-40 parts by weight, the amount of the biodegradable ester polymer is, for example, 50-70 parts by weight, the amount of the masterbatch is, for example, 40-60 parts by weight, and the amount of the compatibilizer is, for example, 1-3 parts by weight.

3. The method according to claim 1, characterized in that: The polyglycolic acid is a homopolymer with a weight average molecular weight of 50,000-300,000, preferably 130,000; the melt index of the polyglycolic acid at 240°C and 2.16kg load is 5-36g / 10min, preferably 26g / 10min; the melting point of the polyglycolic acid is 218-230°C, preferably 220-225°C.

4. The method according to any one of claims 1 to 3, characterized in that: The biodegradable ester polymer is selected from one or more of polylactic acid, polybutylene succinate, polycaprolactone, polycarbonate, polybutylene terephthalate / adipate; and / or The inorganic filler is selected from one or more of talc, silicon dioxide, montmorillonite, clay, calcium carbonate, and microcrystalline cellulose; and / or The coupling agent is selected from one or more of silane coupling agents, phthalates, and maleic anhydride graft copolymers; preferably, the grafting rate of the maleic anhydride graft copolymer is 0.2-5% by weight, preferably 0.5-1% by weight.

5. The method according to any one of claims 1 to 4, characterized in that: The compatibilizer is selected from one or more of epoxy compounds and polyisocyanate compounds; Preferably, the epoxy compound is a copolymer containing a glycidyl methacrylate group, more preferably at least one selected from styrene-acrylonitrile-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer, POE elastomer-glycidyl methacrylate copolymer, styrene-methacrylate-glycidyl methacrylate copolymer; wherein the content of glycidyl methacrylate is 5-15% by weight, preferably 7-12% by weight; Preferably, the polyisocyanate compound is selected from one or more of toluene-2,4-diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, and lysine diisocyanate.

6. The method according to any one of claims 1 to 5, characterized in that: In step (1), the melt blending conditions include: temperature 180-220° C., preferably 190-210° C.; screw speed 50-150 rpm, preferably 70-120 rpm; In step (2), the melt blending conditions include: temperature 220-260° C., preferably 220-250° C.; screw speed 50-150 rpm, preferably 80-120 rpm; Preferably, the method specifically comprises the following steps: drying the raw material before use, firstly blending the biodegradable ester polymer, inorganic filler and coupling agent in step (1) to obtain the masterbatch, and then blending the polyglycolic acid, biodegradable ester polymer, the masterbatch and compatibilizer in step (2) to melt extrude; Further preferably, the drying conditions include: drying temperature of 40-80° C.; drying time of 4-10 h.

7. A biodegradable material prepared by the method according to any one of claims 1 to 6.

8. A method for preparing a biodegradable film, characterized in that: The method comprises the steps of blowing the biodegradable material according to claim 7 to obtain a biodegradable film; Preferably, the film blowing conditions include: a temperature of 180-240° C., preferably 190-220° C.; and a blowing ratio of 1-4, preferably 1.5-3.

9. The biodegradable film prepared by the method according to claim 8.

10. Use of the biodegradable material according to claim 7 or the biodegradable film according to claim 9 in the field of packaging.